Interplanetary Sunnahs Between Salvation and devastation in the Holy Qur’an Intellectual Study (Islamic Sciences Journal, 2023)
This paper deals with the study of the cosmic sunnahs between destiny and salvation through the noble Qur’anic verses as an intellectual study. The second the researcher has talked about the causes of nations’ destruction and their examples and images in the Noble Qur’an, as well as the reasons for nations’ salvation and the lifting of punishment for them, with examples and images spoken by the verses of the Noble Qur’an, and then the conclusion was a summary of the findings. And Praise be to Allah, the Lord of the Worlds.